Metabolic phenotyping of human atherosclerotic plaques: Metabolic alterations and their biological relevance in plaque-containing aorta. (February 2018) - Jung, Sunhee; Song, Suk-Won; Lee, Sak; Kim, Se Hoon; Ann, Soo-jin; Cheon, Eun Jeong; Yi, Gijong; Choi, Eui-Young; Lee, Seung Hyun; Joo, Hyun-Chel; Ryu, Do Hyun; Lee, Sang-Hak; et al.
Abstract: Background and aims: Atherosclerosis is a chronic inflammatory disease characterized by thickening of the arterial wall. However, a limited number of studies have been conducted on metabolic profiling of human aortic tissue. Methods: We applied liquid chromatography/mass spectrometry to perform global and targeted profiling of plaque-containing aortic tissue. The aorta samples included plaque-containing (n = 18) and control plaque-free (n = 24) aortic tissue from patients undergoing aortic surgery. Results: The metabolic patterns of atherosclerotic and control vessels were significantly different. Metabolites in the purine and glutathione pathways showed dysregulation of oxidative stress in plaques, and levels of glucosylceramide, tryptophan, and kynurenine, which are related to inflammation, were also altered. Interestingly, an increased level of quinic acid was observed in plaques ( p < 0.000), and we demonstrated an inhibitory effect of quinic acid on inflammatory activation and oxidative stress in macrophages. Conclusions: Our study provides insight into the disease mechanism and potential markers of atherosclerosis through comprehensive metabolic profiling of human aortic tissue samples containing plaque. Highlights: Metabolic profiling in plaque-containing and plaque-free aortic tissue was applied. The metabolic patterns of atherosclerotic and control vessels were significantly different. Metabolites related to oxidative stress and inflammation were altered in atherosclerotic aorta. Quinic acid level in plaques was increased and its biological effects were demonstrated. Metabolic profiling provides an overview of the metabolic dysregulation in atherosclerotic aorta.